Studi Komparatif Kitab Al-Khil’ah Al-Fikriyyah bi Syarh Al-Minhah Al-Khairiyyah dan kitab Al-Arba’ūna Al-Buldāniyyah Arba’ūna Hadītsan ‘an Arba’īna Syaikhan min Arba’īna Baladan - Khoiri, Khabibul; Purwanto, Purwanto; Mukhlizar, Mukhlizar (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2018)
The study of hadith book is important and must be preserved in order to enrich the knowledge about hadith, one of them is the study of book of Al-Arba'in namely the Al-Fikriyyah Al-Khil'ah book bi Syarh Al-Minhah Al-Khairiyyah by Syaikh Mahfūdz Al-Tirmasī and the book Al-Arba'ūna Al-Buldāniyyah Arba'ūna Hadītsan 'an Arba'īna Syaikhan min Arba'īna Baladan by Syaikh Yasin Al-Fādāī. Based on the results of the study, there are differences in motivation and drafting methods of these two hadith books. The compilation of the Al-Khil'ah Al-Fikriyyah book is due to the existence of the Al-Bukhari Tsulatsiyat book which numbered 22 hadiths, so that the author was motivated to complete it into 40 hadiths which as a whole had a high sanad (isnad ‘ali). While the method of composing the book Al-Khil'ah Al-Fikriyyah was compiled with the names of books starting from Kutub Al-Sittah, Al-Muwatha 'and Tsulatsiyat al-Bukhari. The motivation for compiling the book Al-Arba'ūna Al-Buldāniyyah was that Syaikh Yasin Al-Fadānī should facilitate Muslims in response to the hadith of the Prophet Muhammad. While the method of compiling the book al-Arba'ūna al-Buldāniyyah was the traditions listed therein purely the traditions of the nabawiyyah and arranged in a juz model (part), it made it seemed simpler. The location of the equations of the two books of the hadith is the existence of syarh (explanatory) on each hadith, the number of hadiths, and the sanad that arrived at the Prophet Muhammad. In terms of scientific quality, Sheikh Mahfudz Al-Tirm and Sheikh Yasin Al-Fadani received much recognition from both Arab scholars and the archipelago as scholars who mastered various disciplines, especially Hadith.